Serotype changes and antimicrobial nonsusceptibility rates of invasive and non-invasive Streptococcus pneumoniae isolates after implementation of 10-valent pneumococcal nontypeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) in Bulgaria - Setchanova,Lena (2017)
Abstract The 10-valent pneumococcal conjugate vaccine (PCV10) has been included in Bulgarian Childhood Immunization Program since 2010. This study aimed to assess serotype distribution and antimicrobial resistance of 198 invasive and non-invasive Streptococcus pneumoniae strains that had been isolated in Bulgaria during 2011-2016 from patients with invasive (IPD) and non-invasive (NIPD) pneumococcal diseases. The most common invasive serotypes were 3 (10.1%), 19F (4.0%), and 7F (3.0%). A significant decrease in the proportion of invasive vaccine types (VTs) from 64.2% to 35.2% was found in comparison with pre-vaccine era. The most common serotypes among middle ear fluids were 3, 19A and 19F (5.6% each), and VTs fell down from 66.4% to 40.0% in post-PCV10 period. Among respiratory isolates, the most prevalent serotypes were some emergent serotypes such as 15A/B/C (5.0%), 19A, and 6C (4.0% each). VTs decreased significantly (16.3%) among vaccinated children compared to unvaccinated children and adults (44.0%). Two non-VTs (19A and 6C) have increased significantly more (p < 0.05) in vaccinated children than in unvaccinated patients. The rates of antibiotic nonsusceptible S. pneumoniae in Bulgaria remained high in post-PCV10 era. Among all source of isolates, antimicrobial nonsusceptibility rates were: oral penicillin - 46.5%, trimethoprim-sulfamethoxazole - 45.4%, erythromycin - 43.9%, tetracycline - 37.4%, and multidrug-resistance (MDR) was 44%. The most common MDR serotypes were 19F, 19A, 6A/C, 15A/B/C and 23A. Our results proved that PCV10 vaccination substantially reduced VTs pneumococcal IPD and NIPD. There has been a shift in the distribution of S. pneumoniae serotypes mostly in vaccinated children but also in the whole population and strong serotype-specific antibiotic resistance was observed after vaccine implementation. Therefore, it is important to continue monitoring serotype changes and pneumococcal resistance among all patient ages in addition to aid in determining the long-term effectiveness of PCV10 interventions.